Study on the Integration of Physical and Non-Physical Special Allocation Funds for the Empowerment of Micro, Small, and Medium Enterprises in Sulawesi Utara - Andi Setyo Pambudi (Journal of Business, Finance, and Banking, 2026)
This study is motivated by the phenomenon of Micro, Small, and Medium Enterprises (MSMEs) serving as the backbone of Indonesia’s economy, contributing more than 60 percent to GDP and absorbing 97 percent of the national workforce. However, in the post-pandemic period, most MSMEs face persistent challenges related to market access, financing, and managerial capacity. To address these issues, the government introduced the Special Allocation Fund (DAK) — both physical and non-physical schemes — to strengthen regional entrepreneurship ecosystems. This research aims to assess the contribution of DAK to enhancing production capacity, managerial competence, and institutional strengthening of MSME actors in Sulawesi Utara Province, particularly in Bitung City and Minahasa Utara Regency. A qualitative descriptive approach was employed through Focus Group Discussions (FGDs) and policy document reviews. The findings reveal that DAK has improved production efficiency, financial literacy, and cooperative integration through the development of PLUT (Integrated Business Service Centers) and digital entrepreneurship training. Nevertheless, implementation remains hindered by delayed fund disbursement, weak inter-agency coordination, and limited post-training mentoring. The study recommends strengthening governance, accelerating fund transfers, and adopting results-based evaluation to ensure DAK functions effectively as a catalyst for inclusive and sustainable local economic growth